Ultrasound use in Australasian emergency departments: A survey of Australasian College for Emergency Medicine Fellows and Trainees - Craig, S.; Egerton-Warburton, Diana; Mellett, T. (Blackwell Publishing, 2014)
Objective: To describe current practice of EDUS by ACEM Trainees and Fellows; to describe potential barriers to US use in the Australasian setting; to determine compliance with current college guidelines regarding US credentialing. Methods: Data were collected by a cross-sectional online survey. Respondents were Trainees and Fellows of the ACEM. Outcome measures included the percentage of respondents currently undergoing or that had completed US credentialing for Focused Assessment with Sonography for Trauma (FAST) and assessment of abdominal aortic aneurysm (AAA) scans. The perceived barriers to use of emergency US were explored. Results: There were 512 survey respondents, giving an overall response rate of 15%. Fellows were more likely to be credentialed compared with Trainees. There were 61% of respondents not credentialed for FAST and assessment of AAA scans. However, a significant proportion performed these scans regularly, and did not routinely seek independent confirmation of their findings. Barriers to credentialing included limited time and no credentialing programme at the individual's hospital. Conclusions: The present study showed that only a minority of ACEM Trainees and Fellows are credentialed to perform routine ED scans. Many non-credentialed ACEM Trainees and Fellows are performing scans, many without independent confirmation of their findings.